Liquid Phase Epitaxy for Optical Communication Devices (Bangladesh Journal of Scientific and Industrial Research, 2010)
In this review paper we discuss the scope of the Liquid Phase Epitaxy (LPE) for the growth of the semiconductor materials required for optical communication devices. LPE is non-hazardous comparatively cheaper technology for the material growth and growth processing laboratory could be set up easily. LPE offers the selective and equilibrium growth which is suitable for simple structures. LPE set up could be easily installed for the research and academic institutes as well as in the industries. Key words: Liquid Phase Epitaxy (LPE), Impurities, Optical Communications, Multilayer, Heterostructures, Light Emitting Diodes (LED), Photodetectors, Solar cells and Photodiodes. DOI: 10.3329/bjsir.v44i3.4402 Bangladesh J. Sci. Ind. Res. 44(3), 297-302, 2009